The Implementation of Lean Healthcare As an Effort to Improve The Quality and Patient Satisfaction in Outpatient Services: A Case Study At Bontang Islamic Hospital - Pranoto, Ary Sigit; Kadarisman, Sumeidi; Asnar, Etty Sofia Mariati (Jurnal Sehat Indonesia (JUSINDO), 2025)
This study aims to identify the influence of Lean Healthcare, including service quality, cost, and delivery speed, on patient satisfaction in Rumah Sakit Islam Bontang outpatient services. The sample comprises 376 selected from 6,200 patients using the Simple Random Sampling method. This research employs a quantitative approach with descriptive and verification methods. Data were collected through questionnaires filled out by respondents, and the analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that service quality, cost, and delivery speed significantly affect patient satisfaction both partially and simultaneously. In conclusion, implementing Lean Healthcare has improved patient satisfaction in Rumah Sakit Islam Bontang outpatient services.